1999
DOI: 10.1177/004051759906900208
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Property Relationship of Blended Cotton Yarns Made from Low and High Tenacity Fibers

Abstract: The tensile response of staple yams is usually determined by their structure and the mechanical properties of their constituent fibers. Yarn structure is influenced by the radial disposition of fibers along the yam length, commonly known as migration, and the packing density of the fibers in the yarn cross section. These, in turn, are affected by fiber properties, yarn factors, and the dynamics of preparatory and spinning pro cesses. Yarn structure development is further complicated when the yarn is spun from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 30 publications
1
6
1
Order By: Relevance
“…It followed that for all our yarns, there was no difference in the fiber compactness in different zones. This result did not agree with previous reports [2,22,25,26], where it was observed that the distribution of fiber packing followed a trend of maximum number of fibers in the center and decreasing to reach the minimum number at the outside periphery. The zoning and cutting method differences may explain this result.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…It followed that for all our yarns, there was no difference in the fiber compactness in different zones. This result did not agree with previous reports [2,22,25,26], where it was observed that the distribution of fiber packing followed a trend of maximum number of fibers in the center and decreasing to reach the minimum number at the outside periphery. The zoning and cutting method differences may explain this result.…”
Section: Resultscontrasting
confidence: 99%
“…The migration tendencies according to the blending type (intimate or drawframe) showed similar results to a previous study by Anandjiwala et al [2]. Also, the results presented here confirmed previous results [7] concerning the effects of the fiber characteristics on the fiber distributions in the yarn cross-section, as well as on the migration tendency.…”
Section: Resultssupporting
confidence: 92%
“…On the other hand, the sliverblending method could be an alternative means to manipulate the migration of chitosan fibers in blended yarns. 37 In this case, the cotton fibers in sliver-blended yarns have the tendency to migrate into the core area of the yarn structure, as opposed to cotton fibers in fiber blended yarns.…”
Section: Fiber Distribution In the Blended Yarnsmentioning
confidence: 99%
“…However, Nawaz [10] concluded that the gradual decrease in yarn strength occurs as the share of polyester fibers in the blend decreases. Anandjiwal & Goswami [11] suggested that blending dissimilar fibers lead to their non-uniform distribution throughout the yarn cross section, which in turn, lead to preferential migration depending on both fiber properties and mechanism of spinning process adopted. Therefore, the present study was carried out to figure out the effect of polyester/cotton blend ratio on quality characteristics of resultant yarn.…”
Section: Introductionmentioning
confidence: 99%